2021
DOI: 10.1111/jog.14660
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of recurrent gestational diabetes mellitus: A Japanese multicenter cohort study and literature review

Abstract: Aim To clarify whether maternal characteristics or laboratory parameters could help predict the onset of recurrent gestational diabetes mellitus (GDM). Methods We enrolled 615 women with consecutive singleton deliveries at or after 28 GW from two perinatal medical centers between 2011 and 2019 and divided them into four groups according to whether they had GDM in the first and second pregnancies. The outcome of this study was to clarify the incidence and the predictors of recurrent GDM. Results We found that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…e use of insulin during pregnancy and the family history of diabetes are both high risk factors for abnormal glucose tolerance and recurrence in the second pregnancy, so blood glucose needs to be closely monitored during postpartum follow-up [21]. e higher the FPG and OGTT 2 h values during pregnancy, the more serious the delayed insulin release, and the more obvious the abnormal glucose tolerance after delivery [22].…”
Section: Discussionmentioning
confidence: 99%
“…e use of insulin during pregnancy and the family history of diabetes are both high risk factors for abnormal glucose tolerance and recurrence in the second pregnancy, so blood glucose needs to be closely monitored during postpartum follow-up [21]. e higher the FPG and OGTT 2 h values during pregnancy, the more serious the delayed insulin release, and the more obvious the abnormal glucose tolerance after delivery [22].…”
Section: Discussionmentioning
confidence: 99%
“…The reported frequency of GDM after 4-m preconception LSI was favorably reduced in comparison to that reported in literature; wherein, Rönö et al [28] found the frequency of new GDM was 13% and 17.6% in the first and second pregnancies and the recurrence rate of GDM was 62.8%. Also, Egan et al [29] identified a GDM recurrence rate of 47.6%, and Morikawa et al [30] found the GDM recurrence rate among women who had GDM in the first and second pregnancies was 66.7%.…”
Section: Discussionmentioning
confidence: 99%
“…As the new theory of developmental origins of health and disease (DOHaD) has become generally accepted around the world, a growing number of people consider that nutrition in early life is related closely to fetal and placental development and disease in adulthood 14,15 . Wong et al reported that pre-pregnancy BMI and GWG have a major effect on the recurrence of GDM, including, but not only, cesarean delivery, premature delivery, premature rupture of the membrane, fetal distress, and neonatal jaundice [16][17][18] . Furthermore, the results of Yang et al are consistent with our nding that the interpregnancy interval and FBG level during early pregnancy has a noticeable effect on the recurrence of GDM and pregnancy outcomes [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%